1997
DOI: 10.1073/pnas.94.3.1013
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of stretch-activated cation channels by expression of the α-subunit of the epithelial sodium channel cloned from osteoblasts

Abstract: Osteoblasts respond to repetitive strain by activating stretch-activated, nonselective cation channels (SA-CAT) and increasing matrix protein production. SA-CAT channels are thought to be responsible for mechano-transduction in osteoblasts, although the molecular identity of the SA-CAT channel has previously been unknown. We have demonstrated that both the UMR-106 osteoblast-like cell line and human osteoblasts in primary culture express the α-subunit of the epithelial sodium channel (α-ENaC). The ENaC gene pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 33 publications
5
81
1
Order By: Relevance
“…Through this set of channels mechanical stimulus could induce membrane hyper and de/polarization or a complex multiphasic response. Indeed two stretchactivated membrane channels have been identified in bone cells (Duncan et al, 1996;Kizer et al, 1997). Cyclical strain has been shown to modulate the activity of certain channelschronically strained osteoblasts had significantly larger increases in whole cell conductance when subjected to additional mechanical strain than unstrained controls (Duncan and Hruska, 1994).…”
Section: Channelsmentioning
confidence: 99%
“…Through this set of channels mechanical stimulus could induce membrane hyper and de/polarization or a complex multiphasic response. Indeed two stretchactivated membrane channels have been identified in bone cells (Duncan et al, 1996;Kizer et al, 1997). Cyclical strain has been shown to modulate the activity of certain channelschronically strained osteoblasts had significantly larger increases in whole cell conductance when subjected to additional mechanical strain than unstrained controls (Duncan and Hruska, 1994).…”
Section: Channelsmentioning
confidence: 99%
“…Nonetheless, the mechanosensitivity of ENaC remains a matter of controversy despite a variety of studies attempting to address this issue. Examples of studies in which ENaC appears to be stretch sensitive include the observations that the purified renal ENaC in planar lipid bilayer membranes can be activated by hydrostatic pressure (1,4,8) and that expression of ␣-ENaC in mammalian cells results in stretch-activated channel activity (10). Recent studies have shown that osmotic stretch regulates rat ␣-, ␤-, and ␥-ENaC expressed in Xenopus laevis oocytes (9).…”
mentioning
confidence: 99%
“…Human B Lymphocytes Express the Messages for the ␣ and ␤ Subunits of ENaC-Previous studies have demonstrated that expression of exogenous ␣-ENaC results in a stretch-activated cation channel (9). Nonetheless, we hypothesized that ␣-ENaC may be involved in forming the stretch-activated cation channel observed in human B lymphocytes.…”
Section: Resultsmentioning
confidence: 84%
“…In heterologous expression systems, maximal expression of the hENaC channel requires co-expression of all three subunits (7,8), and in oocytes, expression of ␣-ENaC cRNA alone produces little expression of any amiloride-sensitive currents. However, in other cell types, expression of the exogenous ␣-ENaC subunit alone can form a stretch-activated nonselective cation channel (9), and a similar nonselective cation channel has also been described in native lung epithelial alveolar type II cells (10 -12). This lung cation channel appears to be formed from ␣-ENaC alone and is equally permeable to Na ϩ and K ϩ , is sensitive to steroid hormones, and has a higher unit conductance (21 pS) than that of ␣␤␥-ENaC (4 -5 pS) (13,14).…”
mentioning
confidence: 99%